PENGEMBANGAN MEDIA BMK (BASIC MATHEMATICS FOR KIDS) DALAM PEMBELAJARAN MATEMATIKA UNTUK ANAK USIA DINI 4-5 KELOMPOK B DI RA DARUL FIKRI DAMPIT-MALANG - Nikmahtul Khoir Tri Yulia; Fivi Putri Lestari (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
The development of BMK (Basic Mathematics For Kids) media is very influential on the learning process of early childhood. The purpose of this study is to describe valid, practical, interesting, and effective BMK media through learning mathematics. Researchers used the type of Research and Development (R&D) method used to reveal qualitative and quantitative data (mix method) using data collection techniques in the form of observation, interviews and instruments. The results of the study were seen from media experts 89.7% with the feasibility test classified as valid, material experts 91.2% with the conformity test classified as very suitable, the responsive assessment of students 93.8% with observations classified as very responsive, and the development of learning outcomes from the assessment evaluation. based on 5 indicators including KB1 90%, KB2 91%. KC1 71%, and KC2 77%. This research can be concluded that product development through the trial phase shows the success of the media used in the mathematics learning process is varied-innovative. Also, the ability of the media has a major influence on children's thinking patterns logically-mathematically.